Traces of Chinese Culture in Medan: A Study of Social History and Architecture - Cindy Afriliani; Ribka Anggraiani Br Siregar; Yessi Nanda Pratiwi; Rica Kharomaandini; Pristi Suhendro Lukitoyo (Universitas Syiah Kuala, 2025)
This research aims to examine the traces of Chinese culture in the city of Medan through a social history and architectural approach, by highlighting how the Chinese community shapes, maintains, and represents its cultural identity within the urban space. The qualitative approach was used by field observation methods, in-depth interviews with community leaders and the Chinese young generation, as well as documentation studies of historical buildings and local archives. The results of the study show that the Chinese community in Medan has been present since the late 19th century and plays an important role in the fields of trade, education, and socio-religious life. Their cultural identity is manifested through the existence of religious foundations, educational institutions, and clan-based social structures. Architecturally, the community left behind a legacy of temples, shophouses, and Chinese-classical buildings scattered throughout the Kesawan area and its surroundings. However, many of these buildings have been converted or abandoned due to a lack of preservation regulations. In terms of the younger generation, it was found that there was a shift in cultural identity influenced by modernization and national integration. Although core cultural values are still maintained, the use of regional languages and ritual practices is beginning to decline. This research highlights the importance of preserving Chinese culture as part of the multicultural identity of the City of Medan. Therefore, preservation efforts need to involve partisan policies, cross-generational cultural education, and collective community awareness to maintain the diversity of cultural heritage.